Improvements in hepatitis B virus screening before rituximab therapy: A community‐based, safety‐net hospital experience. Issue 4 (3rd October 2016) - Junus, Kevin; Aguilar, Maria; Patel, Priya; Irwin, David; Yee, Stephen; Liu, Benny; Bhuket, Taft; Wong, Robert J.
Abstract : BACKGROUND: Individuals with chronic hepatitis B virus infection (HBV) or previously resolved HBV are at increased risk of HBV exacerbation or reactivation when they receive treatment with anti‐CD20 monoclonal antibodies (against B‐lymphocyte antigen cluster of differentiation 20 [CD20], an activated‐glycosylated phosphoprotein) like rituximab (RTX). The objective of the current study was to evaluate the rates of appropriate HBV screening before patients started receiving RTX, at the initiation of HBV treatment, and during HBV flares among an underserved safety‐net population. METHODS: In total, 244 consecutive adults who received treatment with RTX from 2006 to 2015 at an urban safety‐net hospital were evaluated to determine appropriate HBV screening (HBV surface antigen [HBsAg] and HBV total core antibody [HBcAb]) before starting RTX. The initiation of prophylactic antiviral therapy and the development of HBV flares after starting RTX were evaluated. Predictors of appropriate HBV screening were evaluated using multivariate logistic regression models. RESULTS: Most patients were women (52.7%; n = 128) and of Hispanic ethnicity (30.7%; n = 74). Before starting RTX, 60.5% (n = 147) of patients received appropriate HBV screening. The HBV screening rates before RTX improved from 14.7% (2006‐2009) to 74.7% (2010‐2012), and to 87.1% (2013‐2015; P  < .01. Two of 7 (28.6%) HBsAg‐positive patients who did not receive antiviral therapy experienced HBV flares and 1 died, and 2 of 27 patients (7.4%) HBcAb‐positive/HBsAg‐negative patients who did not receive antiviral therapy experienced HBV reactivation. No patient‐specific or disease‐specific predictors of receiving HBV screening before RTX therapy were identified. CONCLUSIONS: Among adults receiving RTX therapy in a single community‐based hospital system, HBV screening rates were suboptimal, and 28.6% of HBsAg‐positive patients and 7.4% of HBsAg‐negative/HBcAb‐positive patients who did not receive antiviral treatment experienced HBV reactivation or flare. Cancer 2017;123:650–656. © 2016 American Cancer Society . Abstract : The risk of hepatitis B virus (HBV) reactivation or flare is high among patients with chronic HBV or previously resolved HBV treated with anti‐CD20 therapies. Screening for HBV with both HBV surface antigen and HBV core antibody is important to prevent HBV flares or reactivation, which carry a high morbidity and mortality